2012
DOI: 10.1002/uog.10146
|View full text |Cite
|
Sign up to set email alerts
|

Biometry and fetal weight estimation by two‐dimensional and three‐dimensional ultrasonography: an intraobserver and interobserver reliability and agreement study

Abstract: Objective To evaluate and compare the intraobserver and interobserver reliability and agreement for the biparietal diameter (BPD), abdominal circumference (AC), femur length (FL) and estimated fetal weight (EFW) obtained by two-dimensional ultrasound (2D-US) and threedimensional ultrasound (3D-US). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
2
21
1
1
Order By: Relevance
“…Some studies have attempted to assess the use of 3D volumes to measure 2D distances. These have demonstrated that using 3D imaging to measure biometric variables is reproducible, possibly even more so than 2D scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have attempted to assess the use of 3D volumes to measure 2D distances. These have demonstrated that using 3D imaging to measure biometric variables is reproducible, possibly even more so than 2D scanning.…”
Section: Introductionmentioning
confidence: 99%
“…While the reliability of US-based fetal brain measurements has been examined extensively [11,12,13,14,20], little is known regarding the inter- and intraobserver reliability of MRI measurements of fetal brain malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to fetal US brain measurements, standardized linear measurements for the evaluation of fetal brain on MRI have been proposed [10]. While US reliability in the context of fetal brain measurements has been examined extensively [11,12,13,14], little information exists regarding the inter- and intraobserver reliability of MRI-based measurements of fetal brain malformations.…”
Section: Introductionmentioning
confidence: 99%
“…The model based on biparietal diameter, head circumference, abdominal circumference, femur length and thigh and abdomen volumes proved to be superior to the approach based solely on 2-DUS measurements with biparietal diameter, head circumference, abdominal circumference and femur length as previously described (Campbell and Wilkin 1975;Salomon et al 2011). The 3-DUS measurements were taken in the same manner as 2-DUS measurements, but adjustments in the orthogonal axes were made according to Lima et al (2012). Nardozza et al (2010c) were unable to find statistically significant differences between 2-DUS and 3-DUS calculations using three different models based on 3-D fetal thigh volume, 3-D upper-arm volume or both, after examining 81 Brazilian singleton pregnancies with delivery expected to occur within 48 h. Nonetheless, when 2-DUS and 3-DUS measurements were grouped together, a better estimation of fetal birth weight compared with that obtained with 2-DUS ultrasound measurements alone was obtained (Nardozza et al 2010a).…”
Section: -Dus In Assessment Of Fetal Organ Volume and Estimation Of mentioning
confidence: 99%